Dissociable effects of tDCS polarity on latent decision processes are associated with individual differences in neurochemical concentrations and cortical morphology. (April 2020) - Filmer, Hannah L.; Ballard, Timothy; Ehrhardt, Shane E.; Bollmann, Saskia; Shaw, Thomas B.; Mattingley, Jason B.; Dux, Paul E.
Abstract: Applying a weak electrical current to the cortex has the potential to modulate neural functioning and behaviour. The most common stimulation technique, transcranial direct current stimulation (tDCS), has been used for causal investigations of brain and cognitive functioning, and to treat psychiatric conditions such as depression. However, the efficacy of tDCS in modulating behaviour varies across individuals. Moreover, despite being associated with different neural effects, the two polarities of electrical stimulation – anodal and cathodal – can result in similar behavioural outcomes. Here we employed a previously replicated behavioural paradigm that has been associated with polarity non-specific disruption of training effects in a simple decision-making task. We then used the linear ballistic accumulator model to quantify latent components of the decision-making task. In addition, magnetic resonance imaging measures were acquired prior to tDCS sessions to quantify cortical morphology and local neurochemical concentrations. Both anodal and cathodal stimulation disrupted learning-related task improvement relative to sham (placebo) stimulation, but the two polarities of stimulation had distinct effects on latent task components. Whereas anodal stimulation tended to affect decision thresholds for the behavioural task, cathodal stimulation altered evidence accumulation rates. Moreover, performance variability with anodal stimulation was related to cortical thickness of the inferior frontal gyrus, whereas performance variability with cathodal stimulation was related to cortical thickness in the inferior precentral sulcus, as well as to prefrontal neurochemical excitability. Our findings demonstrate that both cortical morphology and local neurochemical balance are important determinants of individual differences in behavioural responses to electrical brain stimulation. Highlights: There is substantial variability between subjects in response to tDCS. Both anodal and cathodal tDCS can affect performance. We assessed variability & the effect of tDCS on latent decision processes. Anodal and cathodal tDCS modulated performance via different latent processes. Stimulation efficacy related to neurochemical concentrations and cortical thickness.